Infectious and Noninfectious Granulomatosis in Patient with Multiple Sclerosis: Diagnostic Dilemmas and Followup - Jelena Paovic; Predrag Paovic; Vojislav Sredovic (Case Reports in Immunology)
Patient was followed up over the course of 30 years. In 1978, after severe systemic infection followed by fever, pulmonary edema, and numerous neurological manifestations, patient was differentially diagnosed with apoplectic form of multiple sclerosis (MS), which was confirmed a year later via neurological and MRI findings. Approximately 20 years following the initial attack, sarcoidosis was diagnosed during the regular preoperative procedures required for cataract surgery. As consequence of lower immune system, infectious granulomatosis in form of pulmonary tuberculosis developed. Ophthalmological findings revealed bilateral retrobulbar neuritis (RBN) approximately six years after initial attack. This developed into total uveitis with retinal periphlebitis and anterior granulomatous uveitis—all of which are clinically similar in both MS and sarcoidosis.